ENHANCING LESSON EFFECTIVENESS THROUGH INTERACTIVE METHODS - Madina Eshonqulova (Ethiopian International Journal of Multidisciplinary Research, 2025)
This article investigates the role of interactive teaching methods in enhancing the effectiveness of English language lessons. In the contemporary classroom, traditional teacher-centered approaches are gradually giving way to student-centered models that encourage participation, collaboration, and critical thinking. This study examines commonly used interactive strategies and their impact on student engagement, motivation, and academic performance. It also highlights practical examples and implications for foreign language teaching.